Challenges and Opportunities in Developing Sustainable Tourism in Nusa Penida, Indonesia: A Narrative Review of Direct Community Behavior - Suhardono, Sapta; Sianipar, Imelda Masni Juniaty; Suryawan, I Wayan Koko; Septiariva, Iva Yenis; Prayogo, Wisnu (Jurnal Sosial Ekonomi Kelautan dan Perikanan, 2024)
This narrative review aims to evaluate the current situation and challenges of developing sustainable tourism in Nusa Penida, Indonesia, with a focus on direct community behavior. Nusa Penida is a small island located southeast of Bali and is known for its natural beauty and biodiversity. The tourism industry has been growing rapidly in recent years, but it has also brought negative impacts on the environment and the local community. This review examines various studies and reports on the development of sustainable tourism in Nusa Penida and the factors that affect the behavior of local communities, tourists, and tourism stakeholders. The review identifies several challenges to developing sustainable tourism in Nusa Penida, including inadequate infrastructure, limited financial resources, and a lack of effective policies and regulations. The review also highlights the importance of community involvement and empowerment in the sustainable tourism development process. The review suggests that sustainable tourism development in Nusa Penida requires a holistic approach that considers the economic, social, and environmental aspects of tourism. The review further discusses the role of education and awareness-raising in promoting sustainable tourism behavior among local communities, tourists, and tourism stakeholders.